GAMES AND PLAYS CONTRIBUTIONS FOR CHILD DEVELOPMENT IN PHYSICAL EDUCATION CLASSES (Fiep Bulletin - online, 2013)
The Brazilian culture is immeasurable, represented in the literature, in dances, utensil, immaterial representations of the parties, beliefs, gastronomy, plays, among others. Shared by individuals and expressed in their family, economic, religious, political contexts. Mistakenly, believed that culture is transmitted only by adult, forgetting that the kid's playful representations are also a form of cultural transmission and that have a vast repertoire of motor skills for child development. In this way aims to address the importance of using playful culture of games and traditional games for the enhancement of cultural identity and motor performance in school physical education classes. In this context, this question arises: How the cultural and traditional games contribute to the enhancement of cultural identity and the motor performance of children at early Childhood Education? Therefore, the importance of games and plays of the Brazilian popular culture as a form of cultural identity and the motor performance of these children will be evaluated. This study is qualitative by nature, using bibliographic references for theoretical support. The play culture part of the children's cultural heritage, throughout games, plays, toys, music and stories, passed from generation to generation, which are forgotten due to factors such as the appreciation of what is contemporary: the TV, the computer, industrial toys; engines constraints due to lack of public spaces; the social violence. Based on theoretical reference, believing that the educational process must prioritize the access to cultural heritage, throughout a balance between past to present of culture plays, as Physical Education classes, as the science of Human Movement, must ensure the cultural belonging in schools through activities that emphasize, intentionally, the motor skills acquired from the experience in popular culture games, and to make it recognized in the culture.
Keywords: Culture; games and toys; human movement.